Transient electromagnetic detection and numerical simulation analysis of the deformation characteristics of an old goaf in an alpine coal mine area - Wei, Zhan-Xi; Dong, Jian-Hui; Zhao, Meng; Xie, Fei-Hong; Li, Ying-Jun; Feng, Lin (Frontiers in Earth Science, 2023)
In this paper, Qinghai alpine mining area is taken as the research object to explore the deformation characteristics of overlying strata in alpine mining area, so as to prevent geological disasters caused by over-exploitation in alpine mining area. The location of old goaf in coal mine is detected by transient electromagnetic method, and the results are used for numerical simulation. The numerical simulation results show that after coal seam mining, the stress gradually increases from the surface to the bottom, and the stress concentration occurs at both ends and the middle of the mining area. The displacement change area is highly coincident with the stress concentration area, and the displacement monitoring map is consistent with the horizontal displacement cloud map analysis, showing a “U” type distribution. The research results have certain reference value for the future study of surface mining subsidence in inclined coal seams.